Prevalence of high-risk drug-drug interactions in paediatric inpatients: a retrospective, single-centre cohort analysis - Ly Wen Dieu; Anne B. Leuppi-Taegtmeyer; John van den Anker; Daniel Trachsel; Verena Gotta (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY